PENENTUAN PERSENTASE TRANSMISI ERITEMA DAN PIGMENTASI BEBERAPA MINYAK ATSIRI - Widji Soeratri; Noor Ifansyah; Soemiyati; Epipit (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2005)
Prolonged and repetitive skin exposure to the sunlight can cause several disadvantageous effects. The harmful UV radiation of sunlight includes UV-A, which is implicated in tanning, photo aging and UV-B, which is especially responsible for erythema. For protecting the skin against UV light, the pharmaceutical sunscreen products with several active ingredients include natural product-essential oils are used. In this experiment we have investigated the effect of several essential oils as protection of the skin against UV light. The essential oil that used in this experiment were Lavender oil, Kenanga oil, Nilam oil, Geranium oil, Rosemary oil, Neroli oil, and Rose Moroccan oil. The sunscreen effectiveness determination was performed in vitro by determine their percentage of erythema transmission and percentage of pigmentation transmission employed spectrophotometer at wavelength 292.5–372.5 nm. The results showed only lavender oil was effective as sunscreen with the percentage of erythema transmission and percentage of pigmentation transmission was 9.94% and 80.15%, respectively. It was categories as suntan.